Morphometric Analysis of the Iliac Arterial Lengths in Normal and Abnormal Aortoiliac Arteries (Tortuosity,Kinking and Aneurysm) Conditions - Boonruangsri, Porntip; Suwannarong, Bussakorn; Chaisiwamongkol, Kowit; Hipkaeo, Wiphawi; Toomsan, Yanyong; Iamsaard, Sitthichai (Srinagarind Medical Journal, 2015)
Background and Objectives:. The aorta and iliac arteries were the important artery in the abdomen and pelvis. The reports of abnormal (tortousity,kinking and aneurysm) aortoiliac artery in embalmed cadaveric study were still limited. The present study was aimed to measure the lengths of the iliac arteries in normal and abnormal aortoiliac arteries conditions. Methods: Eighty five pelvises of Thai Mongoloids embalmed cadavers were dissected. The cadavers were classified into normal and abnormal aortoiliac arteries. The lengths of the common, external and internal iliac arteries were measured in both groups. All variants data were recorded, photographed and analyzed. The student t- test with significant level of 5 % (p<0.05) was performed to verify the relationship between gender and both groups of arteries in Thai mongoloid embalmed cadavers. Results; We found 41 normal cases (48.2 %) and 44 abnormal cases (51.76%) aortoiliac arteries from 85 pelvis of Thai Mongoloids embalmed cadavers. The average lengths of the common iliac, external iliac and internal iliac arteries in normal groups were 5.19±1.75 cm, 8.05±1.23 cm. and 4.84±1.36 cm., respectively. The average lengths of those arteries in abnormal groups were 4.83±1.41 cm., 8.75±1.37 cm and 5.13±1.34 cm., respectively. There was statistically significant differences of male common iliac and internal iliac arterial lengths between both groups (p<0.05). Conclusion: Our results may have the accuracy to develope the appropriate arterial stent grafts or catheters devices for abdomen and pelvis arteries. Therefore, the complication in abdominopelvic surgery would be decreased if the surgeon have considered the typical lengths of invidual aortoiliac arteries especially in abnormality arterial cases.